(untitled) (Archive of Conferences, 2021)
The article highlights the role and importance of Uzbek folk art in the upbringing and education of young people. And also the author traces the path of development of folk art of Uzbeks throughout the centuries-old tradition. Decrees and decrees of the government of the Republic of Uzbekistan open up new opportunities for the development and support of the unique musical heritage of the Uzbeks